Keluarga sebagai Lingkungan Pendidikan Peletak Budi Pekerti Anak Usia Dini - Thia Isri Yuningsih; Aan Listiana; Ocih Setiasih (Early Childhood: Jurnal Pendidikan, 2023)
This study aims to analyze the role of the family as a foundation of character for early childhood. The method of writing this article is systematic review. The references used in this paper are secondary data in the form of scientific articles searched through the Google Scholar electronic database. References in this study are limited to articles published in the last 10 years. Systematic review consists of three stages, namely identification, evaluation, and interpretation. Based on the identification, evaluation and interpretation, it can be concluded that the laying of character in the family is the core role of parents. Instilling character is the full responsibility of parents for their children, especially early childhood. Planting is important to do early on so that it becomes a habit and will shape the character of a child. Character building in early childhood can be done through advice and examples from parents. Furthermore, the child is guided so that he can practice the values ​​and make it a habit. The child's habits will become the child's character. Parenting style influences the child's character. Democratic parenting is a parenting style that is suitable for instilling character in children